The Existence of Proof of Criminal Liability for Food Poisoning is Reviewed Under the Law Number 18 of 2012 Concerning Food - Heru Susanto; Muhammad Yusuf Siregar; Wahyu Simon Tampubolon; Abdul Hakim (International Journal Labs, 2022)
Background: Developments in the economy, trade, and industry are increasing day by day, this has also given its enjoyment to every consumer because of the large variety of products presented. Objective: This study aims to find out and analyze the criminal responsibility for food poisoning based on law number 18 of 2012 concerning food. As well as knowing and analyzing the existence of evidence against the criminal act of food poisoning. Methods: This research belongs to the normative type of research. So that it can be known that the criminal responsibility for food poisoning is the responsibility of business actors regulated in Article 19 paragraphs (1) and (2) of Law Number 8 of 1999 concerning Consumer Protection. Result: Criminal liability of business actors related to food poisoning is regulated in Article 134 of Law Number 18 of 2012 concerning Food. Furthermore, the proof of the criminal act of food poisoning is that the investigator uses the proof process by taking test results from doctors and labs, visual results, and information from consumers who are victims of food poisoning then reprocessing through the help of BPOM. Conclusion: Based on the conclusion of the criminal liability for food poisoning, the responsibility of business actors are regulated in Article 19 paragraphs (1) and (2) of Law Number 8 of 1999 concerning Consumer Protection.